Aberration of ARID1A Is Associated With the Tumorigenesis and Prognosis of Sporadic Nonfunctional Pancreatic Neuroendocrine Tumors. Issue 4 (April 2020) - Han, Xu; Chen, Wenqi; Chen, Pingping; Zhou, Wentao; Rong, Yefei; Lv, Yang; Li, Jian-ang; Ji, Yuan; Chen, Wei; Lou, Wenhui; Xu, Xuefeng
Abstract : Objective: The genetic aberrations that underlie chromatin remodeling in sporadic nonfunctional pancreatic neuroendocrine tumors (NF-pNETs) remain largely unknown. Here, we investigated the dysregulation of the switch/sucrose nonfermentable (SWI/SNF) component ARID1A and its correlation with clinicopathological features and prognosis. Methods: We sequenced the exomes of sporadic NF-pNETs. Quantitative real-time polymerase chain reaction and immunohistochemistry were used to determine messenger RNA level and protein expression. Results: The sporadic NF-pNETs harbored 264 somatic mutations in 228 different genes, most commonly affecting the SWI/SNF components ARID1B (57.1%) and ARID1A (42.9%). The expression of ARID1A was remarkably downregulated in NF-pNETs and corresponding liver metastases compared with that in normal pancreatic islet tissue. Reduced expression of ARID1A was associated with malignant clinicopathological features ( P < 0.05). The loss of ARID1A was related to a high Ki-67 index ( P < 0.05). Patients with ARID1A -negative expression had a significantly worse overall survival rate than those with ARID1A -positive expression ( P < 0.05). The ARID1A status was an independent predictor of overall survival, and a nomogram integrating ARID1A with clinicopathological features was proposed. Conclusions: The loss of SWI/SNF components ARID1A may be associated with malignant behaviors and an unfavorable prognosis. Aberrations of ARID1A may contribute to tumorigenesis and metastasis in sporadic NF-pNETs.